2007
DOI: 10.4028/www.scientific.net/msf.555.309
|View full text |Cite
|
Sign up to set email alerts
|

Infrared and Photoluminescence Study of Rapidly Thermally Annealed SiO<sub>x</sub> Thin Films

Abstract: Silicon suboxide, SiOx thin films with different oxygen contents (1.15≤x≤1.70) were prepared by thermal evaporation of silicon monoxide at a residual oxygen pressure of 1·10-3 Pa and deposition rates of 0.2, 1.0, 3.0 and 6.0 nm/s. Rapid thermal annealing (RTA) of films was carried out at 1100°C in vacuum for 15 and 30 s and the films were analyzed by infrared (FTIR) and photoluminescence (PL) spectroscopy. In the FTIR spectra of SiOx annealed samples, a blue-shift of the stretching band with initial oxygen con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…In addition, it was also observed that TO mode of the Si-O-Si slightly shifts towards a higher wave number with increasing sintering temperature and time. Similar behaviors of Si-O-Si band in annealed SiO x (x -contents) sample were noticed by many workers [26][27][28]. They pointed out that the peak position of the asymmetric stretching broad band of the SiO x sample depends on the oxygen contents.…”
Section: Ftirsupporting
confidence: 60%
See 1 more Smart Citation
“…In addition, it was also observed that TO mode of the Si-O-Si slightly shifts towards a higher wave number with increasing sintering temperature and time. Similar behaviors of Si-O-Si band in annealed SiO x (x -contents) sample were noticed by many workers [26][27][28]. They pointed out that the peak position of the asymmetric stretching broad band of the SiO x sample depends on the oxygen contents.…”
Section: Ftirsupporting
confidence: 60%
“…They pointed out that the peak position of the asymmetric stretching broad band of the SiO x sample depends on the oxygen contents. Nakamura et al [26] and Milutinovic et al [27] found that the oxygen contents decreases with increasing annealing temperature and time and as a result the peak position shifts towards higher wave number and eventually the density of SiO x increases. Figure 3 shows morphologies of the sintered composites systems (Nd 2 O 3 -SiO 2 ) as viewed under SEM.…”
Section: Ftirmentioning
confidence: 99%
“…In investigation the shifting of the Si-O-Nd peak towards higher spatial frequency is a consequence of higher ionic radius of Nd than Pr. In addition, it was also observed that TO mode the Si-O-Si slightly shifts towards a higher wave number with increasing sintering growth temperature and interruption time [14][15][16]. Fig.…”
Section: Ftirmentioning
confidence: 85%
“…Enzyme impregnated AgNps doped gum acacia-gelatin silica hybrids (H 3 -Enz) shows nearly the same spectrum as that of H 3 indicating immobilization by physical entrapment and not by covalent bonding. In all the IR spectra, bending vibrations due to water are observed at around 1628 cm −1 indicating the hygroscopic character of the powdered samples [44]. Stretching peak due to C O at gum acacia is observed at 1710 cm −1 , which after silver doping shifts to 1705 cm −1 .…”
Section: Characterization Of the Nanohybridsmentioning
confidence: 97%